Why Mars & Venus collide : improving relationships by understanding how men and women cope differently with stress - Gray, John, 1951- (New York : Harper, 2008)
In Why Mars and Venus Collide, Gray focuses on the ways that men and women misinterpret and mismanage the stress in their daily lives, and how these reactions ultimately affect their relationships.
Why Mars and Venus collide -- Hardwired to be different -- Stress hormones -- A woman's never-ending to-do list -- The 90/10 solution -- Mr. Fix-it -- The anatomy of a fight -- How to stop fighting and make up -- Talk about feelings in a fight-free zone -- Looking for love in all the right places -- Creating a lifetime of love -- Reducing stress through cellular cleansing -- Creating the brain chemicals of health, happiness, and romance -- Mars/Venus coaching & counseling.
Includes bibliographical references (p. 235-238).
Keywords: Stress (Psychology); Man-woman relationships; Interpersonal relations